Pengaruh Rasa Percaya Diri Terhadap Motivasi Berprestasi Siswa pada Mata Pelajaran IPA - Asiyah Asiyah; Ahmad Walid; Raden Gamal Tamrin Kusumah (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
This research aims to examine whether there is an influence of self-confidence in students' motivation to achievement in science lesson in elementary schools. This is a field research, where the researchers are involved directly down to the place of research to collect the data relevant to the indicators in the research objectives, which classifies this as a field research with a correlational quantitative approach. Correlational quantitative research is research to determine the level of relations between two or more variables, without making changes, additions, or manipulations of data that already exists. The data analysis techniques was done by observations and questionnaires instruments. Based on the results of analysis with manual calculations, the R Square correlation coefficient is 0.39 or 39% which means that self-confidence affects student motivation for achievement, while the rest is influenced by other variables of 61% that were not examined. This indicates that the variations of confidence with motivation of achievement is 39%. Based on the calculation, the tcount valued 2.898> from ttable, with dk=48, worth 2.011 which means there is an influence of confidence (X) to motivation for achievement (Y). The hypothesis for Ha is accepted and Ho is rejected.